Characterization, Prediction and Analysis of Cytosine Phospho Guanine Islands Genes Related to African Swine Fever Resistance in Pigs - O. O. Oluwole; A. C. Adeola; M. O. Olalere; O. A. Oladejo; A. K. Tiamiyu; A. A. Bolaji; B. A. Boladuro; T. O. Olorungbounmi (Journal of Applied Sciences and Environmental Management)
African swine fever (ASF) has devastating effects on pig populations and the farming  economy. Cytosine phospho Guanine islands (CGIs) are short, unmethylated CpG-rich sequences of many vertebrate genes. They could be linked to ASF disease resistance. Consequently, the objective of this paper was to characterize, predict and analyze Cytosine phospho Guanine islands (CpGIs) genes related to African Swine Fever (ASF) resistance in pigs. Eight genes related to African Swine Fever (ASF) resistance in pigs were analyzed for CGI presence, promoter sites, and phylogenetic relationships with other species. Eight genes involved in ASF disease resistance were selected and downloaded from online databases. Their promoters and CpG islands in their upstream regions were predicted and analyzed using bioinformatic tools. Their genetic distances and phylogenetic trees were also constructed. Bioinformatic tools revealed that the CGIs of these genes were well-conserved, with more exons correlating with a higher number of CGIs and promoters. Phylogenetic analysis showed that warthogs and camels were most closely related to pigs for most genes, except for RFXANK, where goats were the closest. The findings emphasize the role of CGIs in ASF resistance and their potential for epigenetic modifications, aiding in the selection of ASF-resistant pigs to improve production, health, and welfare. The presence of CGIs in these genes associated with resistance to ASF disease highlights the potential for epigenetic modifications to induce beneficial phenotypic changes. The knowledge of these genes are predisposed to such modifications is crucial for researchers, breeding companies, and commercial farmers aiming to select ASF-resistant animals for optimal pig production, health, and welfare.